2021
DOI: 10.1371/journal.pntd.0009079
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a naturally occurring single nucleotide polymorphism in the RagC gene of Leishmania donovani contributes to reduced virulence

Abstract: Leishmaniasis is a widespread neglected tropical disease transmitted by infected sand flies resulting in either benign cutaneous infection or fatal visceral disease. Leishmania donovani is the principal species responsible for visceral leishmaniasis, yet an atypical L. donovani has become attenuated in several countries including Sri Lanka and causes cutaneous leishmaniasis. Previous studies have identified 91 genes altered in the atypical cutaneous L. donovani compared to typical visceral disease associated L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Leishmania TORC1 composition, function and regulation is unknown. Bioinformatic analysis by us and others 7,11,32 identified Leishmania homologues for the key TOR1 complex members TOR, RPTOR1 and LST8 (also found in TORC2) but not for DEPTOR and PRAS40, which associate with these TORC1 members in vertebrates 4,33 . In T. brucei two distinct TOR1 and TOR2 complexes were identified with TORC1 containing TOR1 and RPTOR, and TORC2 containing TOR2 and RICTOR.…”
Section: Discussionmentioning
confidence: 90%
“…Leishmania TORC1 composition, function and regulation is unknown. Bioinformatic analysis by us and others 7,11,32 identified Leishmania homologues for the key TOR1 complex members TOR, RPTOR1 and LST8 (also found in TORC2) but not for DEPTOR and PRAS40, which associate with these TORC1 members in vertebrates 4,33 . In T. brucei two distinct TOR1 and TOR2 complexes were identified with TORC1 containing TOR1 and RPTOR, and TORC2 containing TOR2 and RICTOR.…”
Section: Discussionmentioning
confidence: 90%
“…Although Mm NHEJ mediated repairs can account for a quarter of the total DSB repair events in Mm Ku and Ligase D expressing Leishmania cells, further optimization of Mm NHEJ is needed to improve its DSB repair efficiency for CRISPR gene targeting without using a donor DNA in Leishmania . Depending on whether a heterologous protein is stable, harmless, or toxic, its expression level could vary greatly with time in Leishmania ( 62 ). It appears the proper expression level and ratio of Mm Ku and Ligase D are necessary for making efficient Mm NHEJ repairs since overexpression of Mm Ku alone may inhibit DSB repair ( 20 , 34 , 35 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although two of the SNPs represent silent changes, the other SNP and the InDel would be suggesting a possible co-existence of two proteins, differing each other in two amino acids ( Figure 8 , panel B). If this change in the sequence has a functional role that merits being analyzed, in view of a recent article in which a single amino-acid substitution in the L. donovani RagC protein was found to dramatically affect the virulence of this parasite [ 67 ]. The gene LMJFC_070017800 was annotated as coding for a putative nucleolar RNA-binding protein, but no additional studies on this protein have been reported to date.…”
Section: Resultsmentioning
confidence: 99%